SISTEM PENUNJANG KEPUTUSAN PEMILIHAN HOTEL DI KOTA KENDARI MENGGUNAKAN METODE FUZZY TAHANI BERBASIS WEB - Arisandi Arisandi; Muh. Ihsan Sarita; La Ode Hasnuddin S. Sagala (Informatics Engineering Department of Halu Oleo University, 2016)
The development potential of tourism so rapidly in Southeast Sulawesi is accompanied by the progress of construction of hotels in the city of Kendari . The number of hotels in Kendari offering a variety of amenities and facilities that make the visitors who want to stay difficult to choose the hotel . To assist in the selection of the hotel that fits the needs of visitors it takes a Decision Support System (DSS ) web-based . The system is built using the method of Fuzzy Tahani .the Selection of Tahani Fuzzy method because this method is simpler and easier to understand, but produce the output that is more dynamic. To support the development of this system , use the programming language PHP (Hypertext Preprocessing) and MySQL database. Keywords— Hotel , DSS , Fuzzy Tahani , PHP , MySQL